Spatial inequality in prices and wages: Town-level evidence from the First Globalisation - Stefan Nikolić (European Historical Economics Society (EHES), 2023)
This article leverages uniquely abundant town-level data to examine spatial inequality in prices and wages during the First Globalisation. I build a new dataset on prices of traded and household goods, and wages of skilled and unskilled workers for a panel of 42 towns in Serbia, in the period from 1863 to 1910. I apply the welfare ratio approach to calculate real wages of day labourers and masons. I find strong convergence in grain prices and costs of living, but divergence in wages, both nominal and real. I estimate panel-data models to explore drivers of inter-urban differences in prices and wages. The main results suggest that falling transport costs decreased price gaps, whereas rising population differences increased wage gaps. The findings are consistent with theoretical predictions of new economic geography and urban economics.
Keywords: N33; N73; N93; 330; market integration; grain prices; real wages; Serbia; pre-1913